PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA FIFGROUP DI LUMAJANG - Dimas Julius Hari Kencana; Agustin HP; Bagus Qomaruzzaman Ratu Edi (Program Studi Manajemen, Sekolah Tinggi Ilmu Ekonomi Mandala, 2022)
This study entitled The Influence Of Service Quality On Customer Satisfaction In Fifgroup In Lumajang with the aim of knowing and analyzing the effect of service quality consisting of physical evidence, reliability, responsiveness, assurance and partial empathy on consumer satisfaction at FIFGROUP Yosowilangun Branch Lumajang Regency and to find out and analyzing the effect of service quality consisting of physical evidence, reliability, responsiveness, assurance and empathy simultaneously on customer satisfaction at FIFGROUP Yosowilangun Branch Lumajang Regency. The number of samples in this study was 60 using purposive sampling technique. purposive sampling is a sampling technique using certain criteria. The testing and analysis used in this research is the data instrument test which includes the validity test and reliability test, and the classical assumption test which includes the normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression analysis, the coefficient of determination and hypothesis testing which includes testing t and F test. And the results of this study: 1.) There is no effect of physical evidence on customer satisfaction at FIFGROUP Lumajang 2.) There is no effect of reliability on customer satisfaction at FIFGROUP Lumajang 3.) There is no effect of responsiveness on customer satisfaction at FIFGROUP Lumajang 4.) There is a guarantee effect on customer satisfaction at FIFGROUP Lumajang Branch 5.) There is no influence of empathy on customer satisfaction at FIFGROUP Lumajang. Suggestions from this study to further improve customer satisfaction need to increase again from employees in the company in serving consumers because these employees interact directly with consumers, especially in punctuality as well. So that it will make consumers satisfied and not hesitate to use the company's services again.